# Use completing the square to solve (x – 12)(x + 4) = 9 for x. x = –1 or 15 x = 1 or 7

crosales102   ·   24.09.2019 16:20
28.06.2019 01:00
X> -2 is the simplified version.
26.06.2019 13:40

4.

step-by-step explanation:

it have the same area.brainliest 26.06.2019 10:00

24−3x=−27

step 1: simplify both sides of the equation.

24−3x=−27

24+−3x=−27

−3x+24=−27

step 2: subtract 24 from both sides.

−3x+24−24=−27−24

−3x=−51

step 3: divide both sides by -3.

−3x

−3

=

−51

−3

x=17

x=17

step-by-step explanation:

mark brainliest and have a great day!

08.10.2020 13:01
See below

Explanation:

x^2 - 6x + 5 = 0
(x^2 - 6x + 9) + 5 - 9 = 0
(x - 3)(x - 3) - 4 = 0
(x - 3)^2 = 4
x - 3 = +-2 (sqrt both sides)

x - 3 = 2
x = 5

x - 3 = -2
x = 1
08.10.2020 13:01
OK, here we go
open brackets first,
X²+4x-12x-48=9
x²-8x-48-9=0
x²-8x-57=0
x²-8x=57
x²-8x-4²=57-4²
(x-4)²=57-16
(X-4)²=41
√(x-4)²=+ or -√41
x=4+√41 or x=4-√41
x=4+6.403 or x=4-6.403
x=10.403 or -2.403
x≈ 10.4 or -2.4
08.10.2020 13:01
I hope this helps you 08.10.2020 13:01

x=  10.43398113 ,  -8.43398113

08.10.2020 13:01

we have Group terms that contain the same variable, and move the constant to the opposite side of the equation Complete the square. Remember to balance the equation by adding the same constants to each side Rewrite as perfect squares  therefore 08.10.2020 13:01

x=1+/- the square root of 89

08.10.2020 13:01

I am pretty sure it is C

Step-by-step explanation:

photomath

08.10.2020 13:01

Given the equation: Then; Using the distributive property,  Combine like terms; Subtract 25 from both sides we have; Using completing square form:

Add and subtract we have;  Add 89 to both sides we have; Taking square root both sides we get; Add 1 to both sides we have; Therefore, the values of x are: and 07.06.2020 05:18

The answer is D. 07.06.2020 05:18
(x - 12)(x + 4) = 9
x² + 4x - 12x - 48 = 9
x² - 8x - 48 = 9    |add 48 to both sides
x² - 8x = 57
x² - 2x · 4 = 57    |add 4² to both sides
x² - 2x · 4 + 4² = 57 + 4²    |use (a - b)² = a² - 2ab + b²
(x - 4)² = 57 + 16
(x - 4)² = 73 ⇔ x - 4 = √73 or x - 4 = -√73    |add 4 to both sides

x = 4 + √73 or x = 4 - √73

### Other questions on the subject: Mathematics

Find the greatest common factor of -30x 4 yz 3 and 75x 4 z 2....
Mathematics
21.06.2019 16:30
Yosef can eat 21 jamuns while rose can eat just 15 . complete the blank. yosef can eat % more jamuns than rose....
Mathematics
21.06.2019 17:00
For what value of (y) is 3^3/3^y =1/9...
Mathematics
21.06.2019 19:00
The first side of a triangle measures 5 in less than the second side, the third side is 3 in more than the first side, and the perimeter is 17 in. how long is the third side? if s...
Mathematics
21.06.2019 20:50
Avery’s piggy bank has 300 nickels, 450 pennies, and 150 dimes. she randomly picks three coins. each time she picks a coin, she makes a note of it and puts it back into the piggy b...
Mathematics
21.06.2019 22:30
Hannah reads at a constant rate of 33 pages every 88 minutes. write an equation that shows the relationship between pp, the number of pages she reads, and mm, the number of minutes...
Mathematics
22.06.2019 02:00
Astudent found the solution below for the given inequality. |x-9|< -4 x-9> 4 and x-9< -4 x> 13 and x< 5 which of the following explains whether the student is correc...
Mathematics
22.06.2019 02:30
In the triangle rst, rs = 65 and st = 60. which equation could be used to find the value of angle s?...
Mathematics
22.06.2019 03:00
What integer is equivalent to 9 3/2...
Mathematics
22.06.2019 04:00